Pemenuhan Kebutuhan Keluarga Pasien Kritis dengan Perawatan Paliatif di Intensive Care Unit: Studi di Yogyakarta - Sri Setiyarini; Eri Yanuar Akhmad; Happy Indah Kusumawati (Jurnal Keperawatan Klinis dan Komunitas (Clinical and Community Nursing Journal), 2019)
Background: Regarding the severity of disease, death occur at high rates in ICU, with mortality rate reaches 25%. Hospitalization in ICU has significant impact for patient’s family, therefore meeting needs of family is crucial part in the ICU. Objective: To determine family needs of critically ill patients who need palliative care from nurses and familes perspective.Method: This was descriptive study which conducted in three ICU facilities in Yogyakarta. The subjects were 31 nurses and 76 family members who completed the Critical Care Family Needs Inventory (CCFNI), Meeting Needs Inventory (MNI) instruments and open questions. Data were analyzed quantitatively used mean (± SD) and percentage.Result: The mean (± SD) score of inventory needs (CCFNI) subscale from nurse perception vs. family perception were as follows: assurance (3,488 ± 0,386 vs. 3,602 ± 0,362), proximity and accessibly (3,308 ± 0,363 vs. 3,484 ± 0,739), information (3,207 ± 0,630 vs. 3,334 ± 0,422). The mean (± SD) score of meeting needs (MNI) subscale from perception of nurses vs family were as follows: assurance (3,160 ± 0,371 vs. 3,137 ± 0,556), proximity and accessibly (3,151 ± 0,405 vs. 2,998 ± 0,531), information (2,775 ± 0,399 vs. 2,512 ± 0,630). Conclusion: The most important family need and meeting need, according to nurses and families, is assurance subscale.ABSTRAKLatar belakang: Beratnya jenis penyakit pasien di ICU, membuat ICU menjadi tempat kematian yang umum bagi pasien, dengan angka kematian sekitar 25%. Hospitalisasi di ICU cukup berdampak pada keluarga, sehingga memenuhi kebutuhan keluarga menjadi hal yang penting di ICU. Tujuan: Untuk mengidentifikasi pemenuhan kebutuhan keluarga pasien kritis yang membutuhkan perawatan paliatif, dari persepsi perawat dan keluarga.Metode: Penelitian ini merupakan penelitian deskriptif yang dilakukan di tiga ICU di Yogyakarta. Terdapat 31 sampel perawat dan 76 sampel keluarga pasien yang mengisi instrumen The Critical Care Family Needs Inventory (CCFNI), Meeting Needs Inventory (MNI), dan beberapa pertanyaan terbuka. Data dianalisis secara kuantitatif menggunakan rerata (± SD) dan persentase.Hasil: Skor rerata pentingnya kebutuhan keluarga pasien dari persepsi perawat dan keluarga pada 3 subskala tertinggi, adalah: jaminan 3,488 (± 0,386) dan 3,602 (± 0,362); kedekatan dan akses 3,308 (± 0,363) dan 3,484 (± 0,739); informasi 3,207 (±0,630) dan 3,334 (± 0,422). Rerata terpenuhinya kebutuhan keluarga pasien dari persepsi perawat dan keluarga pada 3 subskala tertinggi, adalah: jaminan 3,160 (± 0,371) dan 3,137 (± 0,556); kedekatan dan akses 3,151(± 0,405) dan 2,998 (± 0,531), informasi 2,775 (± 0,399) dan 2,512 (± 0,630), Kesimpulan: Baik kebutuhan maupun pemenuhan kebutuhan, yang dianggap paling penting menurut perawat dan keluarga adalah jaminan.